The path to a European Health Union - Martin McKee; Anniek de Ruijter (Elsevier, 2024)
Summary: The European Union has historically left health policy decisions to individual member states, cooperating only on issues like cross-border healthcare and medicine safety. However, the COVID-19 pandemic underscored the need for collective action across borders. In response, in October 2020, European Commission President Ursula von der Leyen called for the creation of a "European Health Union". This initiative aims to enhance the protection of European citizens' health, bolster pandemic preparedness, and strengthen healthcare systems. So far, the initiative has not led to major contestation. This might be because the proposals under this heading have been rather piecemeal and are not generally seen as being part of a comprehensive vision for identifying areas where EU intervention benefit national health policy. In this contribution we propose a path forward in terms of content and process for developing a more comprehensive vision on the policy content and the process. In so doing, we are not debating the need for a European Health Union. We take for granted that the existing European Health Union presents an opportunity to deliver, now and in the future, the added benefit of harmonizing, centralizing, or coordinating health-related laws, institutions, policies and actions at EU level.